AMA handbook of business writing the ultimate guide to style, grammar, punctuation, usage, construction, and formatting - Wilson, K. (Kevin) 1958-; Wauson, Jennifer; American Management Association (New York American Management Association, 2010)
This handbook is a complete A to Z reference on everything you need to produce top-quality documents. You'll find more than 600 pages of instantly accessible, thoroughly useful information for getting any job done.
Section 1: The writing process -- Section 2: The business writer's alphabetical reference -- Section 3: Sample business documents.
Electronic reproduction.
Keywords: Commercial correspondence -- Handbooks, manuals, etc; Business writing -- Handbooks, manuals, etc; English language -- Business English -- Handbooks, manuals, etc; Electronic books